Pengaruh Pemberian Kotoran Walet terhadap pH, KTK, C-Organik, N-Mineral dan P-Tersedia pada Tanah Ultisol - Maratun Sholikhah; Afiah Hayati; Akhmad Rizalli Saidy (Acta Solum, 2023)
This study aims to determine the effect of swallow droppings and its best treatment on pH, CEC, organic-C, mineral-N, and available-P in Ultisols. The research method used was a one-factor Completely Randomized Design (CRD) with an incubation period of two weeks, with five treatments of 0, 2.5, 3.0, and 3.5 t ha-1 swallow droppings. Each treatment repeated four times to make 20 experimental units. Parameters observed were soil pH (H2O), CEC, organic-C, mineral-N, and available-P. The results showed that the application of swallow droppings affected pH, CEC, organic-C, mineral-N, and available-P in Ultisols. Swallow droppings of 3.5 t ha-1 significantly affected mineral-N (N-NH4+ and N-NO3-) and other parameters such as CEC, available-P, pH, and organic-C.